Ghana : Economic Development in a Democratic Environment - Harnack, Joachim (Occasional Papers; Occasional Paper, 2000)
This chapter explores the key relationships between participatory democracy and successful economic development and reviews the early steps of participatory decision making in Ghana. More generally, it sets the stage for a discussion of Ghana's main achievements and failures since 1992 in raising the standard of living of its population and reducing poverty. The high-profile political process that launched constitutional democracy in the 1990s and generated Ghana-Vision 2020 placed poverty reduction at the center of economic policy. Based on a set of price and unit labor cost indicators, Ghana's competitiveness improved in the early 1990s through 1994. The evidence for 1995-98 is quite strong. The Bank of Ghana is suspected to have used administrative means and moral suasion to influence the exchange rate, resisting the cedi's depreciation. The terms-of-trade shock forced the Bank of Ghana to focus more clearly on maintaining adequate foreign reserves. The depreciation may then have helped make the foreign exchange market more active and the nominal exchange rate more representative of market conditions.